(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The paper addresses the issue of administrative detention of third-country nationals, highlighting its gradual expansion beyond the scope of irregular migration to also include asylum seekers arriving in the territory of the European Union. The legal framework is examined through the lens of the constitutional requirement that any deprivation of personal liberty be prescribed by law, regarding cases and modalities, as established in Article 13 of the Italian Constitution. Particular attention is given to the application of the principle of extrema ratio in the use of restrictive measures against migrants, as well as to the legislative shortcomings in defining the modalities of detention. A specific focus is also placed on the locations of detention: within the national territory, at the border, and beyond the border.